The Mediating Role of Corporate Governance in the Relationship between the Enterprise Risk Management (ERM) Model and Reducing Business Risks in Jordanian Commercial Banks - Al-Qudah, Laith Akram Al-Qudah (Jordan Journal of Business Administration, 2023)
This study aimed to identify the impact of the Enterprise Risk Management (ERM) model with its various dimensions (internal environment, setting goals, event identification, risk assessment, risk response, control activities, information and communication, monitoring) in reducing business risks in Jordanian commercial banks. In addition, the study aimed to identify the mediating role of corporate governance in the relationship between the Enterprise Risk Management (ERM) model in reducing business risks in Jordanian commercial banks. The population of the study consisted of all 13 Jordanian commercial banks, where the intentional sample method was used for the analysis that represented all 799 branch managers of Jordanian commercial banks. 300 questionnaires were distributed; 282 questionnaires were retrieved and 274 questionnaires were used for data analysis and testing the hypotheses for their validity. Based on the statistical results, the study concluded that there was a statistically significant impact of the Enterprise Risk Management (ERM) model with its various dimensions (internal environment, setting goals, event identification, risk assessment, risk response, control activities, information and communication, monitoring) in reducing business risks in Jordanian commercial banks. However, the internal environment dimension of the Enterprise Risk Management (ERM) model did not make a significant contribution to reducing business risks in Jordanian commercial banks. The study recommended that departments in Jordanian commercial banks develop a time-bound action plan that clarifies the roles and responsibilities related to enterprise-risk management.